Measurement of shock velocity and temperature in laser-shocked carbon disulphide using time-resolved Raman spectroscopy. (January 2022) - Chaurasia, S.; Rao, U.; Mohan, Ashutosh; Pasley, John
Highlights: Time resolved Raman spectroscopy of CS2 under extreme conditions at molecular level has been done. The phase transitions under high pressure has been studies. One dimensional hydrodynamic simulation is performed to validate the experimental data. The resonance Raman effect under the influence of pressure and temperature is measured. The temperature of the sample under shock loading is measured using intensity ratios of stokes and anti-stokes Raman modes of CS2 and the influence of resonance Raman cross section on temperature measurement is also presented. Abstract: High-resolution time-resolved Raman spectroscopy of laser-shocked liquid carbon disulfide (CS2 ) is reported. The symmetric stretching mode (ν1 ) and first overtone of the bending mode (2 ν2 ) of CS2 at 656 cm −1 and 802 cm −1 wavenumbers respectively are analyzed to monitor the possible phase transitions occurring in the sample during shock wave propagation in the pressure range 0.4 – 4.4 GPa by varying the laser intensity on target from 0.2 GW/cm 2 (40 mJ) to 6.4 GW / cm 2 (1300 mJ). A liquid to solid phase transition is observed at 1.5 GPa, as compared to 0.8 GPa in static compression. The difference in these measurements is thought to be due to the high temperatures involved in the dynamic compression experiments described. The shock wave velocities in CS2 at 1.5 GPa and 2.6 GPa are calculated by measuring the intensity ratio of Raman modes emerging from the shocked region to that of the whole sample. 1D radiation-hydrodynamic simulations are performed to corroborate the experimental data. Enhancement of the Raman cross-section of carbon disulfide is observed from 2.5 GPa, which is much lower than the previously reported threshold of 8 GPa as reported by Yoo et al., [24] . This discrepancy in results is thought to be due to the significant contribution of temperature along with the pressure in laser-driven nanosecond single shock experiment.